2000
DOI: 10.1128/.20.17.6600-6611.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Calcineurin-NFATc3-Dependent Pathway Regulates Skeletal Muscle Differentiation and Slow Myosin Heavy-Chain Expression

Abstract: The differentiation and maturation of skeletal muscle cells into functional fibers is coordinated largely by inductive signals which act through discrete intracellular signal transduction pathways. Recently, the calciumactivated phosphatase calcineurin (PP2B) and the family of transcription factors known as NFAT have been implicated in the regulation of myocyte hypertrophy and fiber type specificity. Here we present an analysis of the intracellular mechanisms which underlie myocyte differentiation and fiber ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 32 publications
5
85
0
2
Order By: Relevance
“…durance training can cause dramatic changes in muscle fiber type composition (24). Furthermore, constitutively active MAP kinase kinase 6, an upstream kinase of p38, is reported to promote fast MyHC expression in the presence of forced MyoD expression (38). Meissner (26) also reported that p38 MAPK can regulate MyHC IIx promoter activity yet has little effect on fast MyHC IIa promoter activity (39).…”
Section: Discussionmentioning
confidence: 99%
“…durance training can cause dramatic changes in muscle fiber type composition (24). Furthermore, constitutively active MAP kinase kinase 6, an upstream kinase of p38, is reported to promote fast MyHC expression in the presence of forced MyoD expression (38). Meissner (26) also reported that p38 MAPK can regulate MyHC IIx promoter activity yet has little effect on fast MyHC IIa promoter activity (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports implicating the calcineurin-NFAT pathway during myotube differentiation and fiber type switching encountered difficulties in directly demonstrating NFAT translocation (Delling et al 2000) or the necessity of NFAT-mediated gene expression during these processes (Friday et al 2000;Swoap et al 2000). Factors such as NFAT shuttling dynamics, or the nerve-induced pattern of contractile activity, driving changes in the intracellular Ca 2+ concentration, may be key to the link between calcineurin and NFAT in these studies.…”
Section: Physiological Relevance Of Ache Activation By Nfatmentioning
confidence: 99%
“…(NFATc1) and nuclear translocation of nuclear activated T-cell c3 (NFATc3) (Abbott et al, 1998;Delling et al, 2000) which leads to the transcription of NFAT-dependent genes, including multiple hypertrophic marker genes such as GATA binding protein 2 (GATA-2) ( Fig. 5) (Allen & Leinwand, 2002;Delling et al, 2000;Musaro et al, 1999;Sakuma et al, 2003).…”
Section: Role Of Ca 2] -Dependent Transcriptional Pathways In Skmentioning
confidence: 99%